Особенности восприятия мягкости согласных литовского языка - Балшайтите, Д. (Kalbotyra, 1988)
The present article is concerned with the study of perceptional characteristics of the Lithuanian palatalized consonants when identified by Lithuanians and Russians.Both Lithuanian and Russian listeners recognize all the Lithuanian consonants preceding [u:, o:] as palatalized. The Lithuanian consonants (k’, g’, š’, ž’] (irrespective of the quality of the following vowel) are characterized by the maximum degree of palatalization, the least palatalized are [d’, p’, b’] in the position before [æ, ε].Lithuanian listeners perceive palatalization of the Lithuanian consonants followed by back vowels [u:, o:] better than the Russian ones; Russians identify palatalization of the consonants in the position before front vowels [e:, i:] better than Lithuanians.In some cases Lithuanian listeners do not distinguish palatalization of the Lithuanian consonants; Russians consistently identify stimuli as palatalized and nonpalatalized.